Developing human upper, lower, and deep lung airway models: Combining different scaffolds and developing complex co-cultures - Rasika S Murkar; Cornelia Wiese-Rischke; Tobias Weigel; Sascha Kopp; Heike Walles (Journal of Tissue Engineering)
Advanced in vitro models are crucial for studying human airway biology. Our objective was the development and optimization of 3D in vitro models representing diverse airway regions, including deep lung alveolar region. This initiative was aimed at assessing the influence of selective scaffold materials on distinct airway co-culture models. While PET membranes (30 µm thickness) were unsuitable for alveolar models due to their stiffness and relatively high Young’s modulus, a combination of collagenous scaffolds seeded with Calu-3 cells and fibroblasts, showed increased mucus production going from week 1 to week 4 of air lift culture. Meanwhile standard electrospun polymer membrane (50–60 µm thick), which possesses a considerably low modulus of elasticity, offered higher flexibility and supported co-cultures of primary alveolar epithelial (huAEC) and endothelial cells (hEC) in concert with lung biopsy-derived fibroblasts which enhanced maturation of the tissue model. As published, designing human alveolar in vitro models require thin scaffold to mimic the required ultra-thin ECM, in addition to assuring right balanced AT1/AT2 ratio for biomimetic representation. We concluded that co-cultivation of primary/stem cells or cell lines has a higher influence on the function of the airway tissue models than the applied scaffolds.